Malaria and Typhoid Fever Coinfection among Febrile Patients in Ngaoundéré (Adamawa, Cameroon): A Cross-Sectional Study - Francky Steve Sohanang Nodem; Didiane Ymele; Mouni Fadimatou; Simeon-Pierre Chegaing Fodouop (Journal of Parasitology Research)
Background. Malaria and typhoid fever remain the major cause of morbidity and mortality in tropical and subtropical countries. It is common today to see patients being concurrently infected or treated for the two diseases. Objective. The aim of the present study was to determine the prevalence of malaria, typhoid fever, and their coinfection among febrile patients at Ngaoundéré Regional Hospital, Adamawa, Cameroon. Methodology. A cross-sectional and descriptive study was conducted on 208 febrile patients coming for medical consultation at Ngaoundéré Regional Hospital and suspected for malaria and/or typhoid fever from September to November 2019. After receiving the consent of each patient, clinical and sociodemographic information were collected using a pretested semistructured questionnaire. Thereafter, blood samples were collected and subjected to (i) blood film examination for malaria detection and (ii) qualitative and semiquantitative Widal assay for typhoid fever detection. Results. Plasmodium falciparum was the only species identified, and the prevalence of malaria was 50.0% (n=104). The seroprevalence of typhoid fever was 64.3% (n=133). The malaria and typhoid fever coinfection was 30.3% (n=63). The coinfection between S. paratyphi (A, B, and C) and malaria was also observed with the prevalence ranging from 32.2 to 63.9%. Female group and children from 2 to 10 years old were the most affected groups by the two infectious agents. Conclusion. Typhoid fever and malaria were more prevalent in Ngaoundéré City, particularly in children and women. Further studies should be done on the risk factors of malaria and typhoid fever coinfection in different study areas.